ENHANCING SERVICE QUALITY IN THE AUTOMOBILE BUSINESS: A FOCUS ON KHOREZM REGION (Conferencea, 2024)
The automobile industry is one of the key sectors contributing to economic growth worldwide. In Uzbekistan, the expansion of household incomes and rising automobile ownership rates have heightened the demand for automotive services. This article explores organizational and economic mechanisms for improving service quality in the automobile business, using findings from studies conducted in the Khorezm region.